Cholecystitis suspicion followed by and unexpected diagnosis: a case report - Gonçalves, Maria C.; Gonçalves, Inês C.; Salvado, Mafalda; Diniz, Sara (International Surgery Journal, 2021)
Gallbladder cancer is the 5th most common gastrointestinal cancer, is 2-3 times more frequent in females, and gallstones represent the most important association with this type of cancer. It is generally diagnosed incidentally after cholecystectomy for cholelithiasis and complete surgical resection offers the only potential cure. We report a case of a 42-year-old female, previously healthy, with upper right quadrant pain for 2 weeks and an ultrasound suggestive of cholecystitis. Unfortunately, intraoperative findings were discouraging.